Bridgman growth and characterization of a HoCa4O(BO3)3 crystal. Issue 27 (24th June 2021) - He, Xinchao; Sun, Zhigang; Tu, Xiaoniu; Wang, Sheng; Xiong, Kainan; Chen, Hongbing; Zhang, Xiaoyan; Shen, Liming; Zheng, Yanqing
Abstract : HoCa4 O(BO3 )3 grown with Bridgman method used in QPCPA system. Abstract : RCa4 O(BO3 )3 crystals (RCOB, R stands for rare earth elements) are an excellent class of nonlinear optical crystals. Herein, a 1 inch b -direction HoCa4 O(BO3 )3 (HoCOB) crystal has been grown with the Bridgman method for the first time. The rocking curve was used to study the crystalline quality of the crystal, and the full width at half maximum (FWHM) of the rocking curve was 86.4′′. The monoclinic unit cell parameters were found to be a = 8.0792 Å, b = 16.0114 Å, c = 3.5314 Å, and β = 101.26°, and the unit cell volume was calculated to be 448.0262 Å 3 . The Raman spectra of HoCOB with different orientations were used to analyze the structure. According to the transmission spectrum of the HoCOB crystal, the wavelength of quasi-parametric chirped-pulse amplification (QPCPA) technology application was set. The wavelengths of the three interacting waves were set at 1060 nm (pump), 2255 nm (signal), and 2000 nm (idler), respectively. In addition, the specific heat, thermal diffusion coefficient, and thermal conductivity of the HoCOB crystal were investigated, and it can satisfy the requirements for QPCPA application.